The I–II Loop Controls Plasma Membrane Expression and Gating of Ca(v)3.2 T-Type Ca(2+) Channels: A Paradigm for Childhood Absence Epilepsy Mutations - Vitko, Iuliia (J Neurosci, 2007)
Calcium currents via low-voltage-activated T-type channels mediate burst firing, particularly in thalamic neurons. Considerable evidence supports the hypothesis that overactive T-channels may contribute to thalamocortical dysrhythmia, including absence epilepsy. Single nucleotide polymorphisms in one of the T-channel genes (CACNA1H, which encodes Ca(v)3.2) are associated with childhood absence epilepsy in a Chinese population. Because only a fraction of these polymorphisms are predicted to increase channel activity and neuronal firing, we hypothesized that other channel properties may be affected. Here we describe that all the polymorphisms clustered in the intracellular loop connecting repeats I and II (I–II loop) increase the surface expression of extracellularly tagged Ca(v)3.2 channels. The functional domains within the I–II loop were then mapped by deletion analysis. The first 62 amino acids of the loop (post IS6) are involved in regulating the voltage dependence of channel gating and inactivation. Similarly, the last 15 amino acids of the loop (pre IIS1) are involved in channel inactivation. In contrast, the central region of I–II loop regulates surface expression, with no significant effect on channel biophysics. Electrophysiology, luminometry, fluorescence-activated cell sorting measurements, and confocal microscopy studies demonstrate that deletion of this central region leads to enhanced surface expression of channels from intracellular compartments to the plasma membrane. These results provide novel insights into how CACNA1H polymorphisms may contribute to Ca(V)3.2 channel overactivity and consequently to absence epilepsy and establish the I–II loop as an important regulator of Ca(V)3.2 channel function and expression.